Assessing the effectiveness of parent–child interaction therapy with language delayed children: A clinical investigation. (February 2016) - Falkus, Gila; Tilley, Ciara; Thomas, Catherine; Hockey, Hannah; Kennedy, Anna; Arnold, Tina; Thorburn, Blair; Jones, Katie; Patel, Bhavika; Pimenta, Claire; Shah, Rena; Tweedie, Fiona; et al.
Parent–child interaction therapy (PCIT) is widely used by speech and language therapists to improve the interactions between children with delayed language development and their parents/carers. Despite favourable reports of the therapy from clinicians, little evidence of its effectiveness is available. We investigated the effects of PCIT as practised by clinicians within a clinical setting. Eighteen consecutive children referred for speech and language therapy because of their delayed language were entered in the study. A within-participants design was used, and the procedure was similar to that used clinically. Blind assessments were conducted twice before therapy to monitor change without therapy and once after completing PCIT. Significant changes in a parent rating scale, the children's mean length of utterance and the ratio of time of child to parent speech were found after the therapy. No changes were detected prior to therapy. The similarity of the design to clinical practice and the use of several clinicians suggest that the findings can be generalized to other settings and clinicians. These findings are a first step in evaluating PCIT; we now need to show that parents can maintain their newly acquired skills in interaction, and that this benefits their children's communication.